Pergeseran Sumber Informasi Dari Youtube Ke Tiktok Pada Mahasiswa Ilmu Komunikasi Universitas Nahdlatul Ulama Sulawesi Tenggara - Nicky Astria Windiani, Muslan, Ashar Hasyim, Nana Adriana Hutari (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
Abstract This study aims to find out how the information sources shifting from Youtube to TikTok for Communication Science Students at Nahdlatul Ulama University, Southeast Sulawesi with problem boundaries to observe shifts from media convergence indicators on platforms. The benefit of this research is to see what kind of shift in information sources has occurred. The research location is the Nahdlatul Ulama University of Southeast Sulawesi with the method used is aqualitative method. Determination of informants was determined by purposive sampling of 12 people. Data were collected and analyzed using a qualitative descriptive method. The theory used is the theory of Media Convergence by Henry Jenkins. The results of the study show that the shift in sources of information from Youtube to TikTok among students is subjective depending on the student's need for trends, entertainment and short information. The convergence that occurs is sufficient to explain changes in student preferences for liking TikTok but not sufficient to describe changes in choices in information sources. The needs of students and digitization require them to use multiple platforms as a source of information. Youtube and TikTok have their own advantages so using the platforms together and simultaneously is a must. .